Analysis of Development and Arrangement of Rapid Transit Bus in Public Transport Planning in Gorontalo City - Nainggolan, Jhon Rindu; Siahaan, L Denny; Suhalis, Adenan (Dinasti Publisher, 2024)
System transportation in particular field transport common in the city of gorontalo, is not optimal, thing This can be seen from the characteristics of people who prefer to use bentor (motor tricycles) in carrying out their daily activities compared to using public transportation. For example, the Trans Hulonthalangi BRT (Bus Rapid Transit) has not been used optimally, as well as other public transportation, because object to be researched or data source very large with cover Cluster Sampling (Sampling Area) . Sampling technique area, often used two Step that is first determine the sample area, second determine the people in the area that by sampling too, then n study this using Modeling Techniques Transportation Four Steps (four-step model), and methods collection in the form of primary data network map Street as well as transportation data general, and second secondary data collection with past survey method cross transport road. Could concluded results study this that development and arrangement bus rapid transit in planning transport general in the city of Gorontalo requires 4 (four) corridors with average bus speed 40 Km/Hr: Corridor I long route 20.2 km (PP) requires 9 vehicles with time travel 52.9 minutes, has a headway of 6 minutes and a frequency of 11 vehicles / hour. Corridor II long 9.3 km (PP) route requires 5 vehicles with time travel 26.5 minutes, has a headway of 6 minutes and a frequency of 11 vehicles / hour. Corridor III length the 16 km (PP) route also requires 5 vehicles with time travel 27.6 minutes, has a headway of 8 minutes and a frequency of 8 vehicles / hour. Corridor III length the 16 km (PP) route also requires 5 vehicles with time travel 27.6 minutes, has a headway of 8 minutes and a frequency of 8 vehicles / hour. Corridor long IV the 40 km (PP) route also requires 11 vehicles with time travel 74.8 minutes, has a headway of 6 minutes and a frequency of 11 vehicles / hour.